Updates in the function and regulation of α1-adrenoceptors - Akinaga, Juliana [UNESP]; García-Sáinz, J. Adolfo; S. Pupo, André [UNESP] (Wiley, 2019)
α1-Adrenoceptors are seven transmembrane domain GPCRs involved in numerous physiological functions controlled by the endogenous catecholamines, noradrenaline and adrenaline, and targeted by drugs useful in therapeutics. Three separate genes, whose products are named α1A-, α1B-, and α1D- adrenoceptors, encode these receptors. Although the existence of multiple α1-adrenoceptors has been acknowledged for almost 25 years, the specific functions regulated by each subtype are still largely unknown. Despite the limited comprehension, the identification of a single class of subtype-selective ligands for the α1A- adrenoceptors, the so-called α-blockers for prostate dysfunction, has led to major improvement in therapeutics, demonstrating the need for continued efforts in the field. This review article surveys the tissue distribution of the three α1-adrenoceptor subtypes in the cardiovascular system, genitourinary system, and CNS, highlighting the functions already identified as mediated by the predominant activation of specific subtypes. In addition, this review covers the recent advances in the understanding of the molecular mechanisms involved in the regulation of each of the α1-adrenoceptor subtypes by phosphorylation and interaction with proteins involved in their desensitization and internalization. Linked Articles: This article is part of a themed section on Adrenoceptors—New Roles for Old Players. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.14/issuetoc.